The Resilience of Sharia Microfinance Institutions in Post-Pandemic Recovery: A Case Study of BMTs in Rural Java - Remi Kartina (Tinta Emas Publisher, 2023)
The COVID-19 pandemic created serious economic disruption for micro, small, and medium enterprises in Indonesia, particularly in rural communities with limited access to formal banking services. This study examines the resilience of Sharia microfinance institutions, specifically Baitul Maal wa Tamwil (BMT), in supporting post-pandemic recovery in rural Java. Using a qualitative descriptive approach, data were collected through semi-structured interviews with 15 participants, direct observation at selected BMT offices, and documentation from institutional reports, meeting notes, and local media sources from 2020 to 2022. The findings reveal that BMTs maintained their institutional functions through repayment restructuring, emergency social financing, community-based communication, and the reinforcement of Islamic values. Flexible repayment schemes helped members avoid permanent default, while zakat, infaq, sadaqah, and qard al-hasan supported vulnerable members during periods of economic hardship. The study also shows that social capital, trust, and religious legitimacy were central to BMT resilience. However, BMTs continued to face challenges related to problematic financing, limited digital infrastructure, staff workload, and weak access to external liquidity. This study concludes that BMT resilience is shaped by the interaction of social, religious, and institutional capacities. Strengthening BMTs requires not only financial support, but also improvements in digital systems, governance, human resources, and risk management.